1991
DOI: 10.1073/pnas.88.16.7238
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of high-affinity adenosine A2 receptors decreases the affinity of dopamine D2 receptors in rat striatal membranes.

Abstract: Since high-affinity adenosine A2 receptors (A2u) are localized exclusively in dopamine-rich regions in the central nervous system and mediate inhibition of locomotor activity, we have examined the effect of A2 receptor activation on D1 and D2 receptor binding in membrane preparations of the rat striatum. The A2a agonist 2-p-(2-carboxyethyl)phen- ethylaminoJ-5'-N-ethylcarboxamidoadenosine (CGS 21680) Adenosine has been shown to function as a neuromodulator in many areas of the mammalian central nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
314
1
5

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(335 citation statements)
references
References 37 publications
15
314
1
5
Order By: Relevance
“…We analyzed this cerebral region as some evidence points to the existence of striatal hyperdopaminergic activity secondary to hypofunction of the prefrontal dopamine system [32,33], whereas D 2 R and A 2A R are expressed mainly in medium-sized GABAergic spiny neurons [6]. Interestingly, a recent study showed that, in rodent, ecto-5′-nucleotidase is specifically expressed in this neuronal population, being responsible for most of the extracellular adenosine produced in the striatum [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed this cerebral region as some evidence points to the existence of striatal hyperdopaminergic activity secondary to hypofunction of the prefrontal dopamine system [32,33], whereas D 2 R and A 2A R are expressed mainly in medium-sized GABAergic spiny neurons [6]. Interestingly, a recent study showed that, in rodent, ecto-5′-nucleotidase is specifically expressed in this neuronal population, being responsible for most of the extracellular adenosine produced in the striatum [34].…”
Section: Discussionmentioning
confidence: 99%
“…A 1 Rs and A 2A R are the most expressed receptors in the brain. The modulation of A 1 Rs inhibits presynaptic glutamate release, while postsynaptic A 2A R activation can promote dopamine D 2 receptor signalling inhibition through the heterodimer A 2A R-D 2 R formation [6,7]. Interestingly, a hypoadenosinergic state has been proposed in SZ [8].…”
Section: Introductionmentioning
confidence: 99%
“…A 2A and D 2 receptors form heteromeric complexes with reciprocal antagonistic interactions that regulate the function of the GABAergic enkephalinergic neurons (Ferré et al, 1991(Ferré et al, , 1993(Ferré et al, , 1997Agnati et al, 2003;Canals et al, 2003;Kamiya et al, 2003;Ciruela et al, 2004;Woods and Ferré, 2005). Stimulation of A 2A receptors decreases the affinity of D 2 receptors for agonists by means of an intramembrane interaction (Ferré et al, 1991), while stimulation of D 2 receptors inhibits A 2A receptor-induced activation of adenylyl-cyclase (Kull et al, 1999;Hillion et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of A 2A receptors decreases the affinity of D 2 receptors for agonists by means of an intramembrane interaction (Ferré et al, 1991), while stimulation of D 2 receptors inhibits A 2A receptor-induced activation of adenylyl-cyclase (Kull et al, 1999;Hillion et al, 2002). By means of the strong antagonistic D 2 -A 2A receptor interaction at the adenylyl cyclase level, and due to the existence of a tonic effect of dopamine on D 2 receptors, under normal conditions A 2A receptors are practically unable to activate the cAMP-PKA signaling pathway (Agnati et al, 2003;Ferré et al, 2003Ferré et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the adenosine A,, receptors may be confined to pallidal-projecting GABAergic enkephalin-containing neurons, which also express dopamine D, receptors (Fink et al, 1992;Schiffmann et al, 1991). This is important because an interaction between A,, and D, receptors may play a critically important role for the psychostimulatory effects of caffeine (Ferre et al, 1991). Activation of A,, receptors increases intracellular levels of CAMP , whereas D, receptors mediate the opposite effect on intracellular CAMP levels (Senogles, 1994).…”
mentioning
confidence: 99%